Microlearning for Teaching Faraid, Balaghah, and Qawaid Fiqhiyyah: A Qualitative Study on Instructional Time Constraints - Maskur Maskur; Khalid Al Madani (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2026)
This study aims to examine the effectiveness of implementing the microlearning model in the teaching of religious disciplines within pesantren and madrasah environments. The background of this research lies in the challenges of traditional learning, which are constrained by limited time, the complexity of subject matter, and the need for new approaches that are relevant to the digital context. This study employs a qualitative approach, with data collected through observation, interviews, and document analysis. The results reveal five main findings: (1) limitations in instructional time and material complexity can be addressed through content segmentation; (2) students and teachers respond positively to the microlearning model due to its flexibility and contextual relevance;(3) segmented learning materials are proven to significantly enhance students’ comprehension; (4) the role of teachers has shifted from being the sole source of knowledge to becoming facilitators of digital learning;and (5) microlearning has strategic potential as a technology-based learning approach that aligns with pesantren values. These findings indicate that microlearning not only addresses technical learning needs but also strengthens the role of pesantren in providing adaptive and competitive religious education. This study recommends the development of an integrated and sustainable microlearning-based learning system.